Strategi Perlindungan Hutan Berbasis Hukum Lokal di Enam Komunitas Adat Daerah Bengkulu - Muhammad Yamani (Jurnal Hukum IUS QUIA IUSTUM, 2011)
This research aims to asses values of local law towards forest in six ethnic communities in Bengkulu related to the strategy of forest preservation. This is a normative legal research in a form of local law inventory purposed to find the mechanism of local law in forest preservation in preventive side as well as representative side through impose sanction to the perpetrator of forest destruction. Local law which is effectively regulate in traditional authority has succeeded in engraving moral values to its member which became its justialbelen, where every person by their own awareness actively participate in preserving forest in ulayat area and act carefully based on local forest law. This research purposed to assess the value of local law in six ethnic communities in Bengkulu. From this research we can obtain idea in finding example of legal protection in accordance with local legislation. Furthermore this research may serve as an example for national forest preservation. This research concludes that; first the model of legal protection on local law in six ethnic community of Bengkulu is conducted preventively. Second, the value of local law in ethnic community of Bengkulu can be adopted into local legislations as one of the models of forest preservation in Bengkulu Province through the formulation of academic draft of local legislation.Key words : Forest, custom, local law